2013
DOI: 10.4049/jimmunol.1301597
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK Pathway Is a Predominant Regulator of HLA-A Expression in Esophageal and Gastric Cancer

Abstract: Downregulation of HLA class I expression may contribute to a poor prognosis in cancer patients. There is limited information about epigenetic and oncogenic regulation of HLA class I, and multiple mechanisms may be involved. In the current study, we examined the relationship between the HER2-signaling pathway (MAPK and PI3K-Akt) and the expression of HLA class I and Ag-processing machinery (APM) components. A panel of gastric and esophageal cancer cell lines was treated with wortmannin as an Akt-signal inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 30 publications
4
94
0
1
Order By: Relevance
“…Further, our finding that treatment with the HER2 kinase inhibitor lapatinib alone did not increase but in fact decreased HLA-ABC expression supports lack of an inverse correlation between HER2 kinase activity and HLA-ABC expression. Whereas inhibition of the MAPK pathway, which is downstream of HER2, may increase HLA-ABC expression, as reported by others, 35 treatment of cells with lapatinib can inhibit multiple pathways downstream of HER2 in addition to the MAPK pathway, one of which is the STAT1 pathway. Indeed, we found that the decrease in HLA-ABC expression induced by lapatinib was accompanied by a decrease in the level of phosphorylated STAT1.…”
Section: Discussionmentioning
confidence: 61%
“…Further, our finding that treatment with the HER2 kinase inhibitor lapatinib alone did not increase but in fact decreased HLA-ABC expression supports lack of an inverse correlation between HER2 kinase activity and HLA-ABC expression. Whereas inhibition of the MAPK pathway, which is downstream of HER2, may increase HLA-ABC expression, as reported by others, 35 treatment of cells with lapatinib can inhibit multiple pathways downstream of HER2 in addition to the MAPK pathway, one of which is the STAT1 pathway. Indeed, we found that the decrease in HLA-ABC expression induced by lapatinib was accompanied by a decrease in the level of phosphorylated STAT1.…”
Section: Discussionmentioning
confidence: 61%
“…Most of the studies have shown that MEK inhibition can increase the expression of intrinsic and IFN-γ-induced HLA/ MHC I/II in cancer cell lines, including melanoma, mesothelioma, prostate, gastric, and esophageal cancer cell lines [103][104][105]. Similarly to BRAF inhibition, treatment of mutant melanoma cell lines with MEK inhibition enhances the expression of melanoma-differentiation antigens [92] and decreases the production of IL-10, IL-6, and VEGF [91].…”
Section: Mek Inhibitionmentioning
confidence: 99%
“…Through gene expression, knockdown, chemotherapeutic agents, observation of biologic effect, they identified that over-expression of the p38γMAPK led to marked cell cycle arrest in G2/M phase. What's more, they said the main function of p38γ MAPK in breast cancer was to maintain the oncogenic properties rather than to promote cancer progression (Mimura et al, 2013). All these indicate that p38γ MAPK is a promising target for the design of targeted therapies for basal-like breast cancer.…”
Section: Mapk and Breast Cancermentioning
confidence: 99%
“…In other ways, Kousaku Mimura.et.al proclaimed the MAPK pathway regulated HLA-A expression in gastric cancer (Mimura et al, 2013), while reduced expression of HLA class I on tumors is often associated with disease progression and poor prognosis in diverse human tumors.…”
Section: Mapk and Gastric Cancermentioning
confidence: 99%